Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1677/jme-08-0004
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of hepatic glucocorticoid receptor and hexose-6-phosphate dehydrogenase expression ameliorates diet-induced obesity and insulin resistance in mice

Abstract: Intracellular glucocorticoid (GC) receptor (GR) function determines tissue sensitivity to GCs and strongly affects the development of type 2 diabetes and obesity. 11b-hydroxysteroid dehydrogenase type 1 (11b-HSD1) mediates intracellular steroid exposure to mouse liver GR by prereceptor reactivation of GCs and is crucially dependent on hexose-6-phosphate dehydrogenase (H6PDH)-generating NADPH system. Pharmacological inhibition of 11b-HSD1 improves insulin intolerance and obesity. Here, we evaluated the potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
35
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 52 publications
3
35
0
1
Order By: Relevance
“…The protein concentration was measured by Bradford assay (Bio-Rad Protein Assay Kit). 11␤-HSD1 activity was evaluated by addition of 1 mM NADPH and 250 nmol/l 11-dehydrocorticosterone (11-DHC) with 11-[ 3 H]DHC as tracer to microsomes in KRB solution at 37°C for 1-2 h, as done in our previous study (26). Steroids were separated by TLC, and the percentage of conversion of 11-[…”
Section: Methodsmentioning
confidence: 99%
“…The protein concentration was measured by Bradford assay (Bio-Rad Protein Assay Kit). 11␤-HSD1 activity was evaluated by addition of 1 mM NADPH and 250 nmol/l 11-dehydrocorticosterone (11-DHC) with 11-[ 3 H]DHC as tracer to microsomes in KRB solution at 37°C for 1-2 h, as done in our previous study (26). Steroids were separated by TLC, and the percentage of conversion of 11-[…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, changes in liver GR expression are not evident in other models of insulin resistance, as long-term (i.e. >30 wk) treatment with high-fat diet does not alter liver GR expression and expression of GR target genes [119], indicating that liver GC sensitivity is not always altered under conditions of low whole-body insulin action.…”
Section: Gr and Liver Metabolismmentioning
confidence: 95%
“…On this, while studies have shown that a diabetic-like metabolic phenotype can be partially reversed by GR antagonists and reducing systemic GC levels by adrenalectomy [119][120][121][122], the conclusions from these studies are clouded by the potential off-target effects of these treatments. While whole-body GR deficiency in mice does not alter body-weight gain, impaired glucose tolerance and liver triglyceride accumulation associated with administration of a high-fat diet [89], a recent study has shown that the downregulation of GR mRNA and activity via administration of an 11␤-HSD inhibitor reduced the weight gain, hyperglycemia and insulin resistance in response to high-fat diet feeding in mice [119]. In accordance with this, inhibition of GR expression by agonists for nuclear receptor liver X receptor (LXR) results in an amelioration of the diabetic phenotype in obese, db/db mice [121].…”
Section: Gr and Liver Metabolismmentioning
confidence: 99%
“…11βHSD1 is expressed at high levels in the major organs underpinning metabolism such as liver and adipose tissue. Hepatic overexpression of 11βHSD1 leads to insulin resistance in mice with increased lipogenesis (14), consistent with increased intrahepatic glucocorticoid action, whereas 11βHSD1 inhibition or deficiency leads to decreased hepatic gluconeogenesis (and decreased PCK1), improved insulin sensitivity, and correction of hyperglycemia in rodent models of insulin resistance and patients with T2DM (15)(16)(17)(18).…”
mentioning
confidence: 88%